2019
DOI: 10.1007/s12034-019-1897-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, mechanical and electrical properties of lithium phosphate glasses doped with copper oxide

Abstract: Lithium phosphate glasses with the basic composition (P 2 O 5 50 and Li 2 O 50 mol%) series by the addition of copper oxide (0, 10, 15 and 20 g/100 g) were prepared by a melt quenching technique. Fourier-transform infrared (FTIR) absorption spectra and X-ray diffraction (XRD) analysis were used to characterize the glass samples. Thermal expansion and mass density were also measured. The different mechanical properties of the prepared glasses were measured by an ultrasonic non-destructive technique. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…DC conductivity of the 50Li 2 O-50P 2 O 5 glass with CuO it was reported that an increase in CuO contents and temperature increases the conductivity. For Li 2 O contents and temperature increases, similar conductivity behaviour was observed in our glasses up to 25% mole fraction of Li 2 O (26) . https://www.indjst.org/ Shruthi and Madhu (2021)have reported that from plot log(σ ac )versus log(ω) showed that no dc plateau observed at low frequency region and conductivity was found to be completely frequency dependent as compared to our present glasses exhibited dc conductivity (27) .…”
Section: Conductivitysupporting
confidence: 88%
“…DC conductivity of the 50Li 2 O-50P 2 O 5 glass with CuO it was reported that an increase in CuO contents and temperature increases the conductivity. For Li 2 O contents and temperature increases, similar conductivity behaviour was observed in our glasses up to 25% mole fraction of Li 2 O (26) . https://www.indjst.org/ Shruthi and Madhu (2021)have reported that from plot log(σ ac )versus log(ω) showed that no dc plateau observed at low frequency region and conductivity was found to be completely frequency dependent as compared to our present glasses exhibited dc conductivity (27) .…”
Section: Conductivitysupporting
confidence: 88%
“…They have bone-bonding ability via the formation of a hydroxyapatite layer on their surface and induce angiogenesis [4,5]. To improve their low fracture toughness, which is thought to be the main drawback that restricts the use of BG in load-bearing site applications, polymers, and metal oxides are frequently added to BG [6][7][8][9][10][11][12]. Researchers have attempted to improve the mechanical strength and hardness of burglars, by incorporating different materials into them, including polymers, carbon fibers, and metal oxides [13][14][15].…”
Section: Introductionmentioning
confidence: 99%